Przypadkowy turysta? John Maxwell Coetzee w Europie Środkowej – rekonesans - Kusek, Robert (Śląskie Studia Polonistyczne, 2020)
The article’s aim is to reflect upon the transgenerational and transnational sustainability of Central European memory in literary and cultural space of South Africa. It also investigates links between John Maxwell Coetzee’s oeuvre, as well as works by other South African authors (e.g. Dan Jacobson, Lionel Abrahams, Deborah Levy), with cultural and, above all, literary universe of Central Europe. While analysing selected literary and cultural texts (among others, hitherto unpublished archival documents), the author points to the fact that the Nobel laureate’s consistently and programmatically displayed interest in Central Europe ought to be considered within a wider context of systematic and creative “dialogue” with Central Europe which has been carried out by writers and artists from South Africa in the 20th and 21st centuries. The present study is an original attempt at capturing the phenomenon of mutual cultural flows and horizontal exchange taking place between some minor literatures (and cultures), in this case: South African and Central European.